The Molecular Structure of Alzheimer β‐Amyloid Fibrils Formed in the Presence of Phospholipid Vesicles1. Issue 35 (8th May 2014) - Niu, Zheng; Zhao, Weijing; Zhang, Zhengfeng; Xiao, Fanshu; Tang, Xinqi; Yang, Jun
Abstract β‐amyloid (Aβ) fibrils are the major species involved in Alzheimer's disease (AD). An atomic‐resolution molecular structure of Aβ40 fibrils formed in the presence of lipid vesicles was obtained by using magic angle spinning (MAS) solid‐state NMR spectroscopy. The fibril structures formed in the presence of the lipid vesicles are remarkably different from those formed in solution. These results provide insights into the molecular mechanism of Aβ aggregation in the presence of lipid vesicles.